CADD-31. CD97 PERTUBATION BY NOVEL FUSION PROTEIN DAF-FC INHIBITS GBM INVASION AND INDUCES ANTIBODY DEPENDENT CELLULAR CYTOTOXICITY. (5th November 2018) - Nguyen, Alan; Safaee, Michael; Chandra, Ankush; Wycoff, Keith; Aghi, Manish
Abstract: INTRODUCTION: The poor prognosis of GBM reflects its capacity to supplement proliferative programs with pro-tumoral interactions with the microenvironment, including invasion and immunosuppression. There is a need to simultaneously target these processes, as they can be temporally, mutually exclusive phenotypes toggling back and forth. We have shown CD97 to be upregulated in GBM and capable of mediating each of these pro-tumoral functions in GBM by binding three ligands: decay accelerating factor (DAF/CD55), chondroitin sulfate, and integrins. To validate CD97 as a therapeutic target in glioblastoma, we partnered with an industry collaborator to produce a DAF-Fc fusion protein in a plant expression system combining DAF with IgG1 Fc to block CD97. METHODS: CD97 was targeted with siRNA or DAF-Fc. Scratch and matrigel invasion assays were used to assess migration and invasion, respectively. Antibody dependent cellular cytotoxicity (ADCC) assays used NK-92 human natural killer cells as effector cells and GBM or peripheral blood mononuclear cells (PBMCs) as target cells. Intracranial implantation of glioblastoma cells into athymic mice was followed by DAF-Fc or IgG treatment, with IgG1-Fc detected by immunohistochemistry. RESULTS: CD97 expression was elevated in GBM cells versus astrocytes and lymphocytes, and CD97 knockdown by siRNA reduced migration and invasion by 65–75% (p<0.01). Treatment of human and mouse GBM cells with human and mouse DAF-Fc inhibited migration and invasion by 60–80% (p<0.001). There was increased ADCC against GBM cells with increased DAF-Fc concentration and effector to target ratio (p<0.001), but negligible PBMC toxicity at the highest DAF-Fc dose. Systemically delivered DAF-Fc crossed the blood-brain barrier in orthotopic GBM models with specific tumoral uptake compared to normal brain. CONCLUSIONS: Our results validate DAF-as a GBM therapeutic with negligible off-target effects against normal astrocytes or PBMCs. Further preclinical evaluation in invasive murine models ahead of a phase I trial is underway.